‘Everything is negative’: Schoolteachers’ perceptions of news coverage of education - Shine, Kathryn (2018)
Although education is a staple of news coverage, the reporting of school-based education rarely receives attention within journalism and media studies. Scholars in other areas, however, have argued that news coverage of education is highly influential and should be examined. The research consensus has been that education coverage is mostly negative and, further, that teachers are frequently portrayed as the ones to blame for perceived shortcomings in school systems. Such coverage is said to concern and affect schoolteachers. However, to date, very few studies have canvassed teachers’ attitudes towards the reporting of education. This article contributes to this under-researched area by providing the results of a series of interviews with 25 Australian schoolteachers and principals about their perceptions of news coverage of education. The vast majority of the teachers interviewed considered news about schooling and teachers to be predominantly, and unfairly, critical. They described news reporting of education as frequently inaccurate and generally superficial. Many expressed a distrust of journalists and were wary about being interviewed. The implications of these findings are discussed, and recommendations for journalism practice and journalism education are outlined.